RESERVES FOR THE DEVELOPMENT OF ORGANIZATIONAL CULTURE IN THE CONTEXT OF IMPROVING THE EFFECTIVENESS OF THE EDUCATIONAL INSTITUTION - Sandra Plota (Izdevnieciba "Baltija Publishing", 2021)
The article presents a system of reserves for improving the organizational culture of European educational institutions, ensuring the development of the system of values of educational institutions in response to modern changes and threats, the system of their promotion and adaptation to the changes occurring under the influence of the spread of digital technology and distance learning. This system is based on the principles of social responsibility and academic integrity, the value of academic freedom and culture, and a focus on continuous improvement in the quality of educational services. The following were identified as the main reserves for the development of organizational culture to improve the effectiveness of the educational institution: changing the management style in organizations to ensure a higher quality of educational services and the necessary level of academic culture of all participants in the educational process; ensuring a high level of academic integrity; increasing the level of social responsibility of educational institutions, the introduction of values of social responsibility in their activities; Improving the efficiency of interaction with stakeholders involved in the educational community and building a monitoring system; increasing the involvement of online employees in the activities of the educational institution based on modern distance learning technologies and online communications.